The Face-Name Associative Memory Test as a Tool for Early Diagnosis of Alzheimer’s Disease - Rubiño, José; Andrés, Pilar (Frontiers in Psychology, 2018)
One current challenge for neuropsychologists is to design assessment methods capable of detecting cognitive deficits in the early or preclinical phases of Alzheimer's disease (AD). The objective of this paper is to review the studies that have explored the use of the Face-Name Associative Memory Exam (FNAME) as a test for early diagnosis of AD. Studies looking at correlations between performance on the FNAME test and biomarkers in healthy people and studies comparing healthy controls and people with mild cognitive impairment are reviewed. These studies are based on the evidence that AD’s pathological process begins years before the most visible clinical manifestations. We conclude that the FNAME test may be a valuable tool for early diagnosis but that some important questions remain to be resolved in future research.